Biocontrol Potential of Rhizospheric Bacillus Strains Against Sclerotinia minor Jagger Causing Lettuce Drop - Lihui Xu; Qinghua Shang; Mogens Nicolaisen; Rong Zeng; Shigang Gao; Ping Gao; Zhiwei Song; Fuming Dai; Jingze Zhang (Microorganisms)
Phytopathogenic Sclerotinia minor Jagger causes lettuce drop, a destructive soil-borne disease. As potential biocontrol agents for this disease, 2 of 31 bacterial strains isolated from soil samples from fields containing S. minor Jagger were identified using in vitro antagonistic assays against S. minor Jagger. Bioactivity experiments showed that Bac20 had higher inhibitory activity against S. minor Jagger than Bac45. Based on 16S rRNA sequences and phylogenetic analysis of a combination of sequences from gyrA, rpoB, purH, polC, and groEL, Bac20 and Bac45 were identified as Bacillus velezensis and Bacillus subtilis, respectively. Lipopeptide compounds produced by each strain were identified using matrix-assisted laser desorption ionization–time of flight mass spectrometry (MALDI–TOF MS) analysis. Both strains produced three types of lipopeptides, namely surfactins, iturins, and fengycins, whereas Bac20 showed the strongest intensity in its production of iturins, more than that of Bac45. Bac20 inhibited oxalic acid formation in early-stage lettuce leaves infected with S. minor Jagger, delaying pathogen infestation. Greenhouse experiments for controlling lettuce drop demonstrated that inoculation with Bac20 controlled lettuce drop by 71.7%. In conclusion, this study revealed that B. velezensis Bac20 has high potential for use as a biocontrol agent for controlling the lettuce drop caused by S. minor Jagger.